Paper 01: Quadriceps Tendon Autograft Exhibits Similar Outcomes at Return-to-Sport & Two-Years When Compared to Patellar Tendon Autograft for Primary ACL Reconstruction. Issue 5 (31st May 2022) - Kleihege, Jacquelyn; Calzada, Erik; Polasek, Kimberly; Higbie, Steven; Lowe, Walter; Bailey, Lane
Objectives: Basic science evidence suggests that quadriceps tendon (QT) autograft is a viable alternative to bone-patellar-tendon-bone (PT) autograft for anterior cruciate ligament (ACL) reconstruction due to promising anatomic, histologic, and biomechanical factors. Little evidence exists, however, comparing short and long-term functional outcomes between these two graft sources in a primary setting. The purpose of this study was to compare graft re-injury rates, return to cutting/pivoting sports rates, complications, and self-reported knee function at two years in individuals receiving primary ACL reconstruction with QT versus PT autograft. Methods: A matched case-control study was conducted in accordance with the Strengthening the Reporting of OBservational studies in Epidemiology (STROBE) guidelines using a single-surgeon ACL database of 1, 324 patients to identify 108 (54 PT and 54 QT) patients undergoing primary ACL reconstruction between 2015-2018 (Figure 1). Patients were age and gender matched and between groups comparisons were examined at the time of return to sport and 24 months postoperatively. Data gathered at return to sport included knee range of motion (ROM), single leg squat and single leg hop symmetry, self-reported knee function (IKDC-2000, International Knee Disability Committee), and psychological readiness (ACL-RSI, ACL-Sport After Injury (ACL-RSI). Injury surveillance was conducted for 2-years to determine graft re-injury rates, and at 24-monts level of sports participation, the prevalence of anterior knee pain (Kujala Scale), and self-reported knee function via the Single Assessment Numeric Evaluation (SANE) scores were obtained. Univariate models were utilized to compare groups differences and an alpha of .05 was used to determine statistical significance using SPSS (version 25, IBM Inc., New York, USA). Results: No baseline patient or surgical demographic differences were observed between groups (Table 1). Patients receiving QT autograft had higher single leg squat symmetry (98.2 ±2.8% v 96.1 ±3.0%, P = .001) at time of return to sport. No significant differences existed at time of return to sport (Table 2) regarding knee ROM, single-leg hop test symmetry, self-reported knee function, psychological readiness, or time to return to sport (8.4+ 2.5 mo vs 8.1 ±3.5 mo; P = .486). At two years, there were no significant differences in re-injury rates (0.0% vs 1.2%, P=.383), the prevalence of anterior knee pain, or SANE scores (Table 3). The PT group were significantly more likely to be participating in level I/II (cutting) sports (84.9% vs 69.2%, P =.001) at two years. Conclusions: Patients receiving QT autografts demonstrated comparable self-reported and functional outcomes at time of return to sport and two-year follow-up to those receiving PT autografts. Surgeons should consider utilizing similar rehabilitation timelines and functional performance goals for patients following ACL reconstruction with QT and PT graft options.